Indigenousness in Africa a contested legal framework for empowerment of 'marginalized' communities - Ndahinda, Felix Mukwiza; SpringerLink (Online service). (The Hague, The Netherlands T. M. C. Asser Press, 2011)
Following the internationalisation of the indigenous rights movement, a growing number of African hunter-gatherers, pastoralists and other communities have adopted indigenousness in claiming special legal protection. Their legal claims as the indigenous peoples of Africa are backed by many international actors such as indigenous rights activists, donors and scholars. However, indigenous identification is resisted by many African governments, some community members and some anthropologists. Felix Mukwiza Ndahinda explores the sources of indigenous identification in Africa and its legal and political implications. Noting the limitations of systematic and discursive, as opposed to activist, studies, it questions the appropriateness of this framework in efforts aimed at empowering claimant communities in inherently multiethnic African countries and adopts an interdisciplinary approach in order to capture the indigenous rights phenomenon in Africa.
Electronic reproduction.
Keywords: Indigenous peoples -- Legal status, laws, etc. -- Africa; Electronic books